The Influence of Social Media Use and Parenting Style on Teenagers’ Academic Motivation and Academic Achievement - Kinanti Prabandari; Lilik Noor Yuliati (Journal of Child Development Studies, 2016)
This study aimed to analyze the effects of social media use and parenting styles on teenagers’ academic motivation and academic achievement. The population was grade 11 students of four schools; two schools in Bogor Regency (representative of rural area) and Bogor City (representative of urban area). Samples were 120 students taken by using proportional random sampling. The results showed that the social media use in urban area was higher than that in rural area. Most parents in both regions implemented authoritative parenting style. Intrinsic academic motivation was influenced by authoritative and permissive parenting styles, and duration of social media use. Extrinsic academic motivation was influenced by authoritarian and authoritative parenting styles, and duration of social media use. Teenagers in urban area had better academic achievement than those in rural area, as well as teenage girls compared to teenage boys. Meanwhile, authoritarian parenting style was proved to lower teenagers’ academic achievement.Keywords: academic achievement, academic motivation, parenting style, social media Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media sosial dan gaya pengasuhan orang tua terhadap motivasi belajar dan prestasi belajar remaja. Populasi dalam penelitian ini adalah siswa kelas XI di empat sekolah; masing-masing dua sekolah di Kabupaten Bogor (mewakili wilayah perdesaan) dan Kota Bogor (mewakili wilayah perkotaan). Contoh diambil menggunakan metode proportional random sampling sebanyak 120 siswa. Hasil penelitian menunjukkan penggunaan media sosial remaja di kota lebih tinggi dibandingkan dengan remaja di kabupaten. Sebagian besar orangtua remaja di kedua wilayah menerapkan gaya pengasuhan otoritatif. Motivasi instrinsik dipengaruhi oleh gaya pengasuhan otoritatif dan permisif, serta durasi penggunaan media sosial. Motivasi ekstrinsik dipengaruhi oleh gaya pengasuhan otoritatif dan otoritarian, serta durasi penggunaan media sosial. Remaja di perkotaan mencapai prestasi akademik yang lebih baik dibandingkan remaja di perdesaan, begitu pula dengan remaja perempuan dibandingkan remaja laki-laki. Sementara itu, gaya pengasuhan otoritarian terbukti menurunkan prestasi akademik remaja.Kata kunci: gaya pengasuhan, media sosial, motivasi belajar, prestasi belajar, remaja